Racial and socioeconomic disparity associates with differences in cardiac DNA methylation among men with end-stage heart failure - Pepin, Mark; Ha, Chae-Myeong; Potter, Luke A.; Bakshi, Sayan; Barchue, Joseph P.; Haj Asaad, Ayman; Pogwizd, Steven M.; Pamboukian, Salpy V.; Hidalgo, Bertha A.; Vickers, Selwyn M.; Wende, Adam R. (American journal of physiology. Heart and circulatory physiology, 2021)
Heart failure (HF) is a multifactorial syndrome that remains a leading cause of worldwide morbidity. Despite its high prevalence, only half of patients with HF respond to guideline-directed medical management, prompting therapeutic efforts to confront the molecular underpinnings of its heterogeneity. In the current study, we examined epigenetics as a yet unexplored source of heterogeneity among patients with end-stage HF.